Discontinuity mapping using terrestrial laser scanner and kinematic method - Roslan R.; Omar R.C.; Baharuddin I.N.Z.; Wahab W.A.; Buslima F.S. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This study presents the results of discontinuity mapping using terrestrial laser scanning (TLS) survey and the kinematic method. The results provide the current site and slope condition of comprehensive geological study using terrestrial laser scanning and discontinuity survey at Simpang Pulai, Perak. From the results obtained, it can be concluded that the major potential failures in this area are wedge and plane failures, but there are some area had the potential of toppling failure. This study, however, constitutes a preliminary design consideration and not intended for use in final design or construction. The final design shall be made by the engineer based on the further detail site investigation (S.I.) and other design factors to be used in the actual design of the project. BEIESP.